2009
DOI: 10.1016/j.actbio.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT studies on 3-D bioactive glass–ceramic scaffolds for bone regeneration

Abstract: The aim of this study was the preparation and characterization of bioactive glass-ceramic scaffolds for bone tissue engineering. For this purpose, a glass belonging to the system SiO2-P2O5-CaO-MgO-Na2O-K2O (CEL2) was used. The sponge-replication method was adopted to prepare the scaffolds; specifically, a polymeric skeleton was impregnated with a slurry containing CEL2 powder, polyvinyl alcohol (PVA) as a binding agent and distilled water. The impregnated sponge was then thermally treated to remove the polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 55 publications
4
53
0
2
Order By: Relevance
“…Jones et al [84] recently showed that pore size evaluated by microCT does not always match Hg intrusion porosimetry estimates, and attributed this discrepancy to the mathematical models used to interpret Hg porosimetry data. High-quality microCT images were obtained by Renghini et al [85] using synchrotron radiation as the X-ray source. By combining microCT and computational image analysis, they were able to visualize the formation of different phases on bioactive glass-ceramic scaffolds immersed in tris and SBF (figure 10).…”
Section: (I) N 2 Adsorption and Hg Intrusion Porosimetrymentioning
confidence: 99%
“…Jones et al [84] recently showed that pore size evaluated by microCT does not always match Hg intrusion porosimetry estimates, and attributed this discrepancy to the mathematical models used to interpret Hg porosimetry data. High-quality microCT images were obtained by Renghini et al [85] using synchrotron radiation as the X-ray source. By combining microCT and computational image analysis, they were able to visualize the formation of different phases on bioactive glass-ceramic scaffolds immersed in tris and SBF (figure 10).…”
Section: (I) N 2 Adsorption and Hg Intrusion Porosimetrymentioning
confidence: 99%
“…As summarized in Table 2 [reproduced from (Gerhardt & Boccaccini, 2010)], most of the studies have mainly investigated the mechanical properties, in vitro and cell biological behavior of glass-ceramic scaffolds (Baino et al, 2009;Boccaccini et al, 2007;Bretcanu et al, 2008;Brown et al, 2008;Chen et al, 2007;Chen et al, 2006a;Chen et al, 2008a;Chen et al, 2006b;Deb et al, 2010;Fu et al, 2010;Fu et al, 2007;Fu et al, 2008;Ghosh et al, 2008;Haimi et al, 2009;Klein et al, 2009;Kohlhauser et al, 2009;Mahmood et al, 2001;Mantsos et al, 2009;Miguel et al, 2010;Ochoa et al, 2009;Renghini et al, 2009;Vargas et al, 2009;Vitale-Brovarone et al, 2009a;Vitale-Brovarone et al, 2010;Vitale-Brovarone et al, 2009b;Vitale-Brovarone et al, 2008;Vitale-Brovarone et al, 2004;Vitale-Brovarone et al, 2005;Vitale-Brovarone et al, 2007;Vitale Brovarone et al, 2006). Scaffolds with compressive strength (Baino et al, 2009;Fu et al, 2010) and elastic modulus values (Fu et al, 2010;Fu et al, 2008) in magnitudes far above that of cancellous bone and close to the lower limit of cortical bone have been realized.…”
Section: Clinical Relevancementioning
confidence: 99%
“…For bioactive glass-ceramics, recent developments related to bone tissue engineering scaffolds have been used to remove the gap of load-bearing large bone defects by interplaying between architectures and components carefully designed from comprehensive levels, i.e., from the macro-, meso-, micrometer down to the nanometer scale (Deville et al, 2006), including both multifunctional bioactive glass composite structures and advanced bioactive glass-ceramic scaffolds exhibiting oriented microstructures, controlled porosity and directional mechanical properties (Baino et al, 2009;Bretcanu et al, 2008;Fu et al, 2010;Fu et al, 2008;Vitale-Brovarone et al, 2010). As summarized in Table 2 [reproduced from (Gerhardt & Boccaccini, 2010)], most of the studies have mainly investigated the mechanical properties, in vitro and cell biological behavior of glass-ceramic scaffolds (Baino et al, 2009;Boccaccini et al, 2007;Bretcanu et al, 2008;Brown et al, 2008;Chen et al, 2007;Chen et al, 2006a;Chen et al, 2008a;Chen et al, 2006b;Deb et al, 2010;Fu et al, 2010;Fu et al, 2007;Fu et al, 2008;Ghosh et al, 2008;Haimi et al, 2009;Klein et al, 2009;Kohlhauser et al, 2009;Mahmood et al, 2001;Mantsos et al, 2009;Miguel et al, 2010;Ochoa et al, 2009;Renghini et al, 2009;Vargas et al, 2009;Vitale-Brovarone et al, 2009a;Vitale-Brovarone et al, 2010;Vitale-Brovarone et al, 2009b;Vitale-Brovarone et...…”
Section: Clinical Relevancementioning
confidence: 99%
“…They form a carbonated apatite layer when grafted, which is very similar to bone mineral; this will attract attachment of collagen fibres and eventually should be replaced by host tissue, mineralized matrix and cells. Other scaffolds consist of combinations of poly (lactic-coglycolic acid) (PLGA), alginate and chitosan (Huang &Miao 2007;Jose et al 2009;Mishra et al 2009;Renghini et al 2009). These polymers can also be used to carry cytokines for controlled release at the wound and/or to carry mesenchymal stem cells.…”
Section: Matrix-based Grafts Can Be Autologous Allogeneic or Biomatementioning
confidence: 99%